Tea Bioactive Modulate Innate Immunity: In Perception to COVID-19 Pandemic - Chowdhury, Pritom; Barooah, Anoop Kumar (Frontiers in Immunology, 2020)
Innate immunity impairment led to disruption in cascade of signaling pathways upregulating pro-inflammatory cytokines, diminish interferons, depleted natural killer cells and activate reactive oxygen species production. These conditions severely affected body’s ability to fight against infectious diseases and also plays a pivotal role in disease progression. Here in emphasis is on nutritional immunity for regulating effective innate immune response for combating against infectious diseases like novel coronavirus disease (COVID 19). Drawing from discoveries on in-vitro experiments, animal models and human trials, tea polyphenols ,micronutrients and vitamins has the potential to modulate and enhance innate immune response. This article provides a comprehensive review on tea (Camellia sinensis L) infusion (a hot water extract of dried processed tea leaves prepared from young shoots of tea plant) as an innate immunity modulator. Tea infusion is rich in polyphenols; epigallocatechin gallate (EGCG) and theaflavin (TF), major green and black tea polyphenols, respectively. Studies showed their immunomodulatory competence. Tea infusions are also rich in alkaloids; caffeine and its intermediates, theophylline and theobromine, which have anti-inflammatory properties. Tea plant being an acidophilic perennial crop can accumulate different micronutrients, viz. copper (Cu), iron (Fe), manganese (Mn), selenium (Se) and zinc (Zn) from growing medium i.e. from soil, which led to their considerable presence in tea infusion. Micronutrients are integral part of innate immune response. Overall, this review presents tea infusion as an important source of nutritional immunity which can enhance innate immune response in order to mitigate the unprecedented COVID-19 pandemic.